Ammonia and nutritional therapy in the critically ill: when to worry, when to test and how to treat?. Issue 2 (March 2023) - Redant, Sebastien; Warrillow, Stephen; Honoré, Patrick M.
Abstract : Purpose of review: Hyperammonaemia is almost always develops in patients with severe liver failure and this remains the commonest cause of elevated ammonia concentrations in the ICU. Nonhepatic hyperammonaemia in ICU presents diagnostic and management challenges for treating clinicians. Nutritional and metabolic factors play an important role in the cause and management of these complex disorders. Recent findings: Nonhepatic hyperammonaemia causes such as drugs, infection and inborn errors of metabolism may be unfamiliar to clinicians and risk being overlooked. Although cirrhotic patients may tolerate marked elevations in ammonia, other causes of acute severe hyperammonaemia may result in fatal cerebral oedema. Any coma of unclear cause should prompt urgent measurement of ammonia and severe elevations warrant immediate protective measures as well as treatments such as renal replacement therapy to avoid life-threatening neurological injury. Summary: The current review explores important clinical considerations, the approach to testing and key treatment principles that may prevent progressive neurological damage and improve outcomes for patients with hyperammonaemia, especially from nonhepatic causes.